K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 7 2018

\(1)\left(x+1\right)^3-\left(x-1\right)^3-6\left(x-1\right)\left(x-1\right)\\ =x^3+3x^2+3x+1-x^3+3x^2-3x+1-6\cdot\left(x-1\right)^2\\ =6x^2+2-6\cdot\left(x^2-2x+1\right)\\ =6x^2+2-6x^2+12x-6\\ =12x-4\)

\(2)x\left(x-1\right)\left(x+1\right)-\left(x+1\right)\left(x^2-x+1\right)\\ =x\left(x^2-1\right)-\left(x^3+1\right)\\ =x^3-x-x^3-1\\=-x-1\)

\(3)\left(x-1\right)^3-\left(x+2\right)\left(x^2-2x+4\right)+3\left(x-4\right)\left(x+4\right)\\ =x^3-3x^2+3x-1-(x^3+8)+3\cdot\left(x^2-16\right)\\ =x^3-3x^2+3x-1-x^3-8+3x^2-48\\ =3x-55\)

26 tháng 8 2018

Thanks bạn

4 tháng 9 2019

\(1a,P=\left(x+2\right)^3+\left(x-2\right)^3-2x\left(x^2+12\right).\)

\(=x^3+6x^2+12x+8+x^3-6x^2+12x-8-2x^3-24=0\)

\(b,Q=\left(x-1\right)^3-\left(x+1\right)^3+6\left(x+1\right)\left(x-1\right)\)

\(=x^3-3x^2+3x-1-x^3-3x^2-3x-1+6\left(x^2-1\right)\)

\(=-6x^2-2+6x^2-6=-8\)

14 tháng 10 2019

1,\(2x\left(x-5\right)-\left(x-2\right)^2-\left(x+3\right)\left(x-3\right)\)

\(=2x^2-10x-x^2+4x-4-x^2+9\)

\(=\left(2x^2-x^2-x^2\right)+\left(-10x+4x\right)+\left(-4+9\right)\)

\(=-6x+5\)

2,\(\left(x+1\right)^2-3\left(x-5\right)\left(x+5\right)-\left(2x-1\right)^2\)

\(=x^2+2x+1-3\left(x^2-25\right)-\left(4x^2-4x+1\right)\)

\(=x^2+2x+1-3x^2+75-4x^2+4x-1\)

\(=-6x^2+6x+75\)

3,\(\left(x-1\right)^3-\left(x-3\right)\left(x^2+3x+9\right)\)

\(=\left(x-1\right)^3-\left(x^3-27\right)\)

\(=x^3-3x^2+3x-1-x^3+27\)

\(=-3x^2+3x+26\)

4,\(\left(x+5\right)\left(x^2-5x+25\right)-\left(x+2\right)^3\)

\(=\left(x^3+125\right)-\left(x^3+6x^2+12x+8\right)\)

\(=x^3+125-x^3-6x^2-12x-8\)

\(=-6x^2-12x+117\)

5,\(2x\left(x-7\right)-\left(x+3\right)\left(x-2\right)^2+\left(x+1\right)^2\)

\(=2x^2-14x-\left(x+3\right)\left(x^2-4x+4\right)+x^2+2x+1\)

=\(2x^2-14x-x^3+4x^2-4x-3x^2+12x-12+x^2+2x+1\)

\(=-x^3+4x^2-4x+1\)

6,\(\left(2x+5\right)\left(x-3\right)-\left(x+5\right)\left(x-1\right)-\left(x-4\right)^2\)

\(=2x^2-6x+5x-15-x^2+x-5x+5-x^2+8x-16\)

\(=3x-26\)

7,\(\left(x+5\right)\left(x-5\right)\left(x+2\right)-\left(x+2\right)^3\)

=\(\left(x^2-25\right)\left(x+2\right)-x^3-6x^2-12x-8\)

\(=x^3+2x^2-25x-50-x^3-6x^2-12x-8\)

\(=-4x^2-27x-58\)

Nếu đúng thì tick cho mk nha ^_^